2014
DOI: 10.1021/jo402443w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Photochemistry of 3-Methyl-2-phenyl-2H-azirine and 2-Methyl-3-phenyl-2H-azirine

Abstract: Photolysis of 3-methyl-2-phenyl-2H-azirine (1a) in argon-saturated acetonitrile does not yield any new products, whereas photolysis in oxygen-saturated acetonitrile yields benzaldehyde (2) by interception of vinylnitrene 5 with oxygen. Similarly, photolysis of 1a in the presence of bromoform allows the trapping of vinylnitrene 5, leading to the formation of 1-bromo-1-phenylpropan-2-one (4). Laser flash photolysis of 1a in argon-saturated acetonitrile (λ = 308 nm) results in a transient absorption with λ(max) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 53 publications
3
31
2
Order By: Relevance
“…Although ketenimine formation is considered characteristic of the reactivity of triplet vinylnitrenes in cryogenic matrices, we did not observe any new IR bands that could be assigned to ketenimine formation following irradiation of 1 in argon matrices. The calculated IR spectrum of ketenimine 6 (Figure D) has a characteristic band corresponding to the C=C=N stretch at 2049 cm −1 after scaling.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…Although ketenimine formation is considered characteristic of the reactivity of triplet vinylnitrenes in cryogenic matrices, we did not observe any new IR bands that could be assigned to ketenimine formation following irradiation of 1 in argon matrices. The calculated IR spectrum of ketenimine 6 (Figure D) has a characteristic band corresponding to the C=C=N stretch at 2049 cm −1 after scaling.…”
Section: Resultscontrasting
confidence: 73%
“…Because triplet alkylnitrenes and arylnitrenes have high spin properties and are long‐lived, they have a potential as building blocks for high spin assemblies. In contrast, triplet vinylnitrene intermediates are short‐lived in solution, in spite of their electron‐donating substituents, because they decay by intersystem crossing to form azirines and isoxazoles . Triplet vinylnitrenes react differently from alkylnitrenes and arylnitrenes because they have significant 1,3‐biradical character, which makes rotation around the vinyl bond feasible, and it has been theorized that intersystem crossing is facilitated by this rotation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,61,[64][65][66] The triplet vinylnitrenes were observed in recent experiments. 24,66,[98][99][100] In contrast, the n → π * excitation of the imine chromophore, promoted at shorter wavelengths, should result in the C 2 -C 3 bond cleavage and produce the nitrile ylide intermediate through an internal conversion to a vibrationally hot ground state. As shown in Figure 2(b), the isomerization from the nitrile ylide to oxazole owns a lower barrier (ca.…”
Section: Mechanistic Aspectmentioning
confidence: 99%
“…[21][22][23] In fact, the preference of the C-C over C-N photocleavage depends on the nature of substituents and their positions in the azirine ring, besides the applied wavelength. 24,25 With respect to the C-N single bond photocleavage, it has been proposed to proceed by a mechanism involving triplet intermediates that were formed through an intersystem crossing from an excited singlet state. [21][22][23][24][25][26] Our previous calculation, however, showed that the C-N single a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%